Role of PU.1 Expression as an Inflammatory Marker in Experimental Autoimmune Uveoretinitis. (18th August 2018) - Umazume, Akihiko; Kezuka, Takeshi; Matsuda, Ryusaku; Usui, Yoshihiko; Takahashi, Hiroki; Yamakawa, Naoyuki; Yashiro, Takuya; Nishiyama, Chiharu; Goto, Hiroshi
ABSTRACT: Purpose : PU.1 is an Ets family transcription factor, which is essential for the development of immune system through generation of myeloid and lymphoid lineages. In this study, we investigated PU.1 expression in the retina of mice with experimental autoimmune uveoretinitis (EAU) and the association between PU.1 expression level and inflammation in EAU. Methods : IRBP 1–20 peptide-immunized mice were used. Quantitative PCR, ELISA analysis, cytometric bead array (CBA), assay and immunostaining were conducted using ocular tissues and lymph nodes. Results : Quantitative PCR showed significant increases in mRNA levels of PU.1 in the retina at the peak of inflammation. Immunostaining of retina flat mounts revealed that most PU.1-positive cells were co-stained with anti-CD11c and anti-F4/80 antibodies. PU.1 knockdown in lymph node cells significantly suppressed IRBP-stimulated IFN-γ production measured by ELISA and IL-2 production measured by CBA. Conclusion : PU.1 may play crucial roles in the development and progression of inflammation in EAU.